2020
DOI: 10.21203/rs.3.rs-77015/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Academic Anxiety and Self-handicapping Among Medical Students During the COVID-19 Pandemic: A Moderated Mediation Model

Abstract: Background: The outbreak of 2019 coronavirus disease (COVID-19) could increase the risk of academic anxiety among medical students. Research has revealed that academic anxiety was a risk factor for self-handicapping, however, little is known about the underlying mechanisms that may mediate or moderate this association. This study examined the mediating role of procrastination and moderating role of hardiness in the association between academic anxiety and self-handicapping during the COVID-19 pandemic.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
2
20
1
2
Order By: Relevance
“…Our findings also demonstrated that procrastination was higher in Time 1 than in Time 2, though the difference in procrastination was not significant between the two time periods. While our results cannot conclude that procrastination levels were higher during the pandemic than before (Aucejo et al, 2020;Biricik and Sivrikaya, 2020;Jia et al, 2020), our finding showed that procrastination was higher during the initial phases of the pandemic than in the subsequent phases, suggesting that sudden changes brought about by COVID-19 played a part in encouraging procrastination. The lack of significant difference in procrastination may be an artifact of the similarity in environmental uncertainty levels.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Our findings also demonstrated that procrastination was higher in Time 1 than in Time 2, though the difference in procrastination was not significant between the two time periods. While our results cannot conclude that procrastination levels were higher during the pandemic than before (Aucejo et al, 2020;Biricik and Sivrikaya, 2020;Jia et al, 2020), our finding showed that procrastination was higher during the initial phases of the pandemic than in the subsequent phases, suggesting that sudden changes brought about by COVID-19 played a part in encouraging procrastination. The lack of significant difference in procrastination may be an artifact of the similarity in environmental uncertainty levels.…”
Section: Discussioncontrasting
confidence: 69%
“…Taking it all together, existing studies established that COVID-19 has resulted in a preponderance of procrastination among students in higher education (Aucejo et al, 2020;Biricik and Sivrikaya, 2020;Jia et al, 2020); yet, they do not elucidate how COVID-19 have effected an increase in procrastination. Drawing upon previous findings and employing a life history framework (Griskevicius et al, 2013;Del Giudice et al, 2015;Chen and Qu, 2017), we propose that the increase in procrastination may be attributed to the heightened levels of uncertainty in the pandemic.…”
Section: The Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The anxiety experienced by students regarding lessons during the Covid-19 pandemic can lead to academic procrastination behavior ( Jia, Jiang, & Lin, 2020). The results of researchers' observations on Indonesian students showed an increase in academic procrastination behavior.…”
Section: Introductionmentioning
confidence: 96%
“…Several variables related to procrastination have been identified, such as academic anxiety, self-handicapping, and COVID-19 fear in students. An explanation is that students could only study online given the imposed lockdowns, thus providing a more favorable context to procrastinate [ 8 , 10 , 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%